PENGARUH PENDAPATAN DAN BEBAN OPERASIONAL TERHADAP LABA BERSIH PADA DAVID WATER MEDAN - Yanti S.SE,MM; Mayu Rina Dwita; Nadiya Ulfa (Yayasan Cita Cendikiawan Al Kharizmi, 2026)
The background of this final project report is to determine the net profit of a business. This is because businesses usually do not know their net profit and only use ordinary accounting methods. David Water Medan is a business engaged in the sale of refillable drinking water. The purpose of this study is to determine the extent to which revenue and operational expenses influence net profit at David Water Medan, a small and medium-sized enterprise (SME) located at Jl. Chaidir, Nelayan Indah, Kec. Medan Labuhan, Kota Medan, North Sumatra 20524. In this study, David Water employs a quantitative research method. Quantitative data, which is obtained from structured or patterned research results, is easier for researchers to interpret. Quantitative research presents information in numerical or nominal form. The population and sample in this study consist of financial statements from three periods between 2020 and 2022. Data collection was in the form of documentation from financial reports at David Water Medan. David Water is classified as a small business because it has three employees. This study shows that revenue and operating expenses have a significant impact on net profit. This is evidenced by the fact that as revenue increases and operating expenses rise, the profit obtained decreases. If revenue increases and operating expenses decrease, the profit obtained also decreases.